The potential of a legal doctrine of competitive geopolitics: an analysis of the Preamble of the Constitution of the Republic of Latvia - Svarinskis, Jānis Artūrs (Riga Graduate School of Law, 2020)
Geopolitical competitions and hybrid warfare continue to develop in complexity and invasiveness of state sovereignty as cyberspace, culture, economy, and other fields become weaponized in place of traditional military power. In this thesis, the author discusses the potential for jurisprudence to directly recognize the practices of competitive geopolitics. This is to ensure their effective regulation, with particular potential in human rights. The thesis, firstly, defines a purpose of the law based on the reasonings of select landmark legal philosophers. Secondly, the thesis establishes a working definition of the ambiguous concept of “geopolitics” based on the contributions of statesmen and scholars of the field. Additionally, the thesis proposes a new concept, competitive geopolitics, to separate the competitive interpretation from the overarching concept of geopolitics. Thirdly, the thesis analyzes the Preamble of the Constitution of the Republic of Latvia for the presence of competitively geopolitical provisions, with mixed results.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Public law::Constitutional law; Latvia